Clostridium difficile infection in cystic fibrosis: an uncommon but life‐threatening complication. Issue 1 (7th December 2016) - Piccolo, Francesco; Tai, Anna Sze; Ee, Hooi; Mulrennan, Siobhain; Bell, Scott; Ryan, Gerard
Abstract : Adults with cystic fibrosis (CF) have significant rates of asymptomatic Clostridium difficile carriage and are frequently exposed to risk factors for C. difficile infection (CDI). Despite this, the rate of reported CDI in CF is low. We describe three cases of near fatal CDI in adults with CF and review the literature regarding presentation, management, and recurrence prevention. Early recognition is important as the clinical presentation may be atypical and the illness can be severe and even life‐threatening. Management can be complicated by respiratory and nutritional failure. CF‐related gastrointestinal dysfunction may alter the typical host–pathogen interaction between patient and C. difficile, potentially explaining the low rates of CDI and atypical presentation. Abstract : Adults with cystic fibrosis (CF) have significant rates of asymptomatic Clostridium difficile carriage and are frequently exposed to risk factors for C. difficile infection (CDI). Despite this, the rate of reported CDI in CF is low. We describe three cases of near fatal CDI in adults with CF and review the literature regarding presentation, management and recurrence prevention. Early recognition is important as the clinical presentation may be atypical and the illness can be severe and even life‐threatening. Management can be complicated by respiratory and nutritional failure. CF related gastrointestinal dysfunction may alter the typical host‐pathogen interaction between patient and C. difficile potentially explaining the low rates of CDI and atypical presentation.